EXAMINING GENDER MICROAGGRESSIONS IN ACADEMIC SETTINGS: AN ANALYSIS OF TYPES AND FACTORS CONTRIBUTING TO GENDER INEQUALITY AMONG TEACHERS IN SCHOOLS - Nur Fadhilah Umar; Rafli, Muhammad; Mentari, Nindah Nurul; Rahayu, Hastriani; Fahira, Nur (Counsenesia Indonesian Journal Of Guidance and Counseling, 2023)
This study aims to develop a scale to analyze the causes of most of the occurrence of gender bias behavior caused by microaggressions and identify what forms of gender bias are carried out by perpetrators of microaggressions against recipients. This type of research is a descriptive quantitative research. The population in this study were elementary school teachers in Makassar City. The sampling technique in this study used simple random sampling. The sample in this study was 100 elementary school teachers. The technique of collecting data in this study uses 1) The Gendered Racial Microaggressions Scale (GRMS) instrument; 2) Instruments for microaggression factors that have been tested through Confirmatory Factor Analysis (CFA) are declared feasible. Data analysis techniques used descriptive statistical tests and Structural Equation Modeling (SEM). The results showed that: (1) The most common form of microaggression is microaggression caused by gender bias, especially aspects of stereotypes and concern for certain genders. In addition, microaggression is caused by two factors, namely internal (cultural awareness) and external factors (colleagues, family culture and social media). Based on the findings obtained, it is necessary to optimize gender awareness in basic education units through education, positive family education patterns from an early age, and curved use of social media.